From Serendipity to Strategy: Rationalizing Molecular Glue Discovery and Proximity-Induced Pharmacology through Chemical Biology. - Gray,JL; Xiao,Z; Rogga,VV; Zhang,X; Tate,EW (J Am Chem Soc, 2026)
Molecular glues represent a new paradigm in drug discovery, stabilizing novel protein-protein interactions between two proteins to elicit targeted cellular outcomes. Historically discovered through serendipity, molecular glue identification is becoming increasingly systematic. In this perspective, we discuss the current advances and challenges of this field, highlighting the transition toward rational discovery through the convergence of four complementary approaches. Innovations in library design and screening platforms are expanding access to glue-relevant chemical space, guided by a deeper mechanistic understanding of proximity-induced pharmacology. These efforts are further enabled by functional genomic approaches that reveal gluable interfaces. Finally, the integration of chemical and biological data through machine learning is beginning to support rational de novo glue design.